2018
DOI: 10.1097/icl.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corneal Scars and Their Treatment With Rigid Contact Lenses on Quality of Vision

Abstract: Corneal scars can have a strong effect on quality of vision by diminishing visual acuity and increasing straylight. The increase in straylight from corneal scars on its own can lead to a serious visual handicap. Contact lens treatment did not improve straylight, but showed a slight worsening. As the recovery of visual acuity with contact lens wear far exceeded straylight increase, contact lenses remain a clinically useful treatment option in most patients with corneal scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Additionally, rigid corneal lenses allow for much greater tear exchange compared to scleral lenses, especially a sealed one, so atmospheric oxygen should be more available to the cornea with this approach [49,50], just as a SiHy lens is likely to allow for better tear exchange than a sealed scleral lens [51]. Rigid corneal lenses are useful in the visual rehabilitation of corneal scars because their capacity to neutralise any corneal irregularity outweighs any worsening of straylight [52]. Nevertheless, the prescribing of rigid corneal lenses has lost some favour for cosmetic purposes and for corneal disease cases in recent years because of the challenges associated with fitting this modality and because many patients find scleral lenses more comfortable [53].…”
Section: Rigid Corneal Lensesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, rigid corneal lenses allow for much greater tear exchange compared to scleral lenses, especially a sealed one, so atmospheric oxygen should be more available to the cornea with this approach [49,50], just as a SiHy lens is likely to allow for better tear exchange than a sealed scleral lens [51]. Rigid corneal lenses are useful in the visual rehabilitation of corneal scars because their capacity to neutralise any corneal irregularity outweighs any worsening of straylight [52]. Nevertheless, the prescribing of rigid corneal lenses has lost some favour for cosmetic purposes and for corneal disease cases in recent years because of the challenges associated with fitting this modality and because many patients find scleral lenses more comfortable [53].…”
Section: Rigid Corneal Lensesmentioning
confidence: 99%
“…Rigid corneal lenses can be considered for visual rehabilitation in scarred corneas and with corneal opacities after trauma or infection [52,[460][461][462]. More recently, semi-scleral contact lenses provide excellent visual acuity and comfort in patients with such irregular corneas [441, 463].…”
Section: Irregular Astigmatism From Infection Trauma Dystrophy or Degenerationmentioning
confidence: 99%
“…Mihranyan et al took advantage of carboxylated cellulose nanowhiskers to enhance the mechanical properties of polyvinyl alcohol (PVA) for replacing conventional contact lenses. It was suggested that this combination could be flexible and have suitable optical properties [100]; however, constant usage of the contact lenses can cause corneal scar [101,102].…”
Section: Growth Factor Deliverymentioning
confidence: 99%
“…Korneal skar dokusu hem yarattığı opaklık hem de düzensiz astigmatizma nedeni ile görme keskinliğinde azalmaya neden olmakla beraber, sert kontakt lensle bu hastaların görme keskinliklerinin 20/20 seviyesinde bile bulunabileceği bilinmektedir. 32 Biz de çalışmamızda bu hastaların görme keskinliklerinin 20/200-20/40 aralığında olabileceğini öngördük, ancak elimizde net veri olmadığı için istatistiksel değerlendirmeye dâhil etmedik.…”
Section: Gereç Ve Yöntemlerunclassified